The lived theology of the Harry Potter series - Apostolides, Anastasia (HTS teologiese studies, 2014)
This article will argue that the recent turn towards lived theology or religion in practical theology can offer a useful hermeneutic to interpret the impact of the Harry Potter series on the spiritual formation and identity creation of adolescents. In practical theology there has been a turn towards lived theology or religion as lived religion has moved out of institutions into social–cultural phenomena as people seek to find meaning and purpose for their lives in alternative places to institutionalised religion.